Heavy mineral variations in Campano-Maastrichtian sandstones in the northern Bida Basin and their provenance -tracing implication - Suraju Adesina Adepoju; Olusola Johnson Ojo (Discover Applied Sciences)
Abstract This study employs heavy mineral dataset to provide spatial relationships among source area, erosional, and sediments deposition in the northern part of Bida Basin, Nigeria. Weight percentages of both opaque and non-opaque minerals examined from eighty sandstone samples as determined by optical and cathodoluminescence (CL) analyses reveal lateral variation from southwestern to central and northern parts. The mineralogical-textural relationships evaluation reveal abundance of colorless to brownish, subhedral to anhedral, equant to prismatic Zircon grains at the western and southwestern areas, while acicular, weathered and corroded varieties dominated the central and northern parts. Bluish and greenish Tourmaline varieties are very common at the western and southwestern parts while light brownish and yellowish types dominated the central and northern parts. Also, there were records of more irregular and conchoidal Rutile varieties at the southwestern parts while knee-shaped, deep red, brownish and deep brownish colorations were dominant at the central and northern parts. Evidence from Zircon elongation ratios shows the presence of two distinct Zircon populations; long and short which may suggest two provenance areas. Morphological features of zircon with euhedral to subhedral, prismatic, lamellar, boundary zoning, well-developed oscillatory zone, concentric zoned, xenocrystic cores and Sillimanite inclusion indicate a felsic rock from a magmatic crystallization of tectonically stable passive continental margin. Brownish to deep red knee-shaped Rutile and irregular, greenish to bluish and golden to straw yellow Tourmaline with sub-rounded, sub-conchoidal fractured and etches garnet indicate mixed type of acidic and intermediate igneous and metamorphic rocks within orogenic provenance. In this study, it is concluded that the variations in the heavy mineral characteristics from the southwestern and western parts towards the central and northern parts of the northern Bida Basin imply that sediments were mainly sourced from southwestern part of the northern Bida Basin.